Automation Concepts for Industrial-Scale Production of Seaweed - Solvang, Torfinn; Bale, Emil Scott; Broch, Ole Jacob; Handå, Aleksander; Alver, Morten Omholt (Frontiers in Marine Science, 2021)
In order to industrialize macroalgal cultivation in Norway, new automated methods and solutions for seeding, deployment and harvesting need to be developed. Today's solutions are time and resource demanding, still yielding volumes nationally in the range of 100–200 tons per year in total (not including wild harvest), while the potential is in the megaton range. Standardization of equipment and automation can be one way to upscale production. Here we present results from a design study of a module-based solution for industrial cultivation, with specific solutions for spinning of thin seedling strings onto longlines, and a robotic module for interaction with the submerged farm at deployment and harvest. A reduced-scale physical prototype of the farm concept with the robot has been built for testing of deployment and harvesting techniques. The concept has been named SPOKe: Standardized Production of Kelp.